Promoting pre-service EFL teacher reflection: An investigation of reflection levels in Thai context - Swatevacharkul, Rosukhon (Indonesian Journal of Applied Linguistics, 2019)
Reflection is essential for the teaching practice course since it enhances life-long professional teaching development of the teachers. Capacity to reflect needs to be developed. The objectives of this study were 1) to investigate the levels of learning reflection of pre-service EFL teachers at the end of the teaching practice course, and 2) to explore how reflection contributes to changes of the reflection levels.  This study took the form of an embedded experimental mixed methods research design using a close and open-ended questionnaire and semi-structured interview to collect data from 13 international students at an MA ELT program.  Data analysis was performed by a t-test and thematic content analysis.  The findings revealed that 1) on average, the level of Habitual Action, Understanding, and Critical Reflection at the beginning and the end of the course was not significantly different. However, the level of Reflection was significantly different at the end of the course.  Three themes: 1) Revision of past experiences for teaching improvement; 2) Thinking and writing skills development, and 3) Change of beliefs and teaching techniques were generated causing such reflection capacity changes.  Recommendations were provided for further research in this area.